THE LEVEL OF CUSTOMER SATISFACTION WITH THE MARKETING MIX (9P) IN KOPI NAKO SLIPI - Djauharie, M. Edo Nanda Pratama; Muhaimin, Abdul Wahib; Haryati, Novi; Maulidah, Silvana (Socio-Economics/Agribusiness Department, 2023)
Marketing strategy is a way to gain competitive advantage for companies that produce goods or services. The importance of analyzing the value of the level of customer satisfaction with the company's marketing mix to determine the characteristics of consumers, the level of importance and performance of the company's marketing mix and the level of customer satisfaction. With this research, it is hoped that the company can improve and develop its marketing strategy and provide recommendations to improve the performance of the marketing mix (9P). This research uses a descriptive quantitative approach and was conducted in December 2021-February 2022. The research method used is Importance Performance Index and Customer Satisfaction Index. The research respondents were 90 people using purposive sampling method and processed using SPSS 26 and Microsoft Excel. Based on the results of the Importance Performance Analysis, the overall results have an average value of the indicator suitability level at the Nako Slipi Coffee Shop of 91.37 %. This value is included in the good category. However, the indicator performance level has not reached 100% so that the store needs to improve the performance indicators of the marketing mix attributes which are still unsatisfactory, especially on the promotional media indicator (X4.2). Based on the results of the analysis using the Customer Satisfaction Index, the general level of customer satisfaction is 87.20 % and is included in the very satisfied category. This explains that most consumers are very satisfied with the performance of the marketing mix attributes (9P) carried out by the Nako Slipi Coffee Shop in general.